Combinatorics : the Rota way - Kung, Joseph P. S. (Cambridge mathematical library., 2009)
Gian-Carlo Rota was one of the most original and colourful mathematicians of the 20th century. Written by two of his former students, this book is based on notes from his influential graduate courses and on face-to-face discussions.